A baseline assessment of beach macrolitter and microplastics along northeastern Atlantic shores - Velez, Nadja (2020)
Marine litter is widely dispersed throughout coastal environments. Assessing the distribution and accumulation of such contaminants is crucial to understand their environmental impacts. This study presents a baseline for the monitoring of litter and microplastics in intertidal sediments along the Atlantic shores of southern Portugal and Morocco and identifies potential sources of contamination. Although variable, distribution and composition of both litter and microplastics did not follow a latitudinal pattern. Most of the litter had an undifferentiated source. Within the identifiable sources of litter, food packaging, fishing and tobacco were the most abundant, with variable contributions among sites. Over 97% of marine litter retrieved was plastic. Fragments and filaments were the most abundant categories of plastics at sites with the highest and lowest microplastic abundance respectively. Filaments were mainly made of Polypropylene (PP,50%) and Polyethylene terephthalate (PET,29%) while the predominant polymers for fragments were Polyethene (PE, 75%) and PP (25%).